Clinicopathological and functional significance of RECQL1 helicase in sporadic breast cancers - Arora, Arvind; Parvathaneni, Swetha; Aleskandarany, Mohammed A.; Agarwal, Devika; Ali, Reem; Abdel-Fatah, Tarek; Green, Andrew R.; Ball, Graham R.; Rakha, Emad A.; Ellis, Ian O.; Sharma, Sudha; Madhusudan, Srinivasan (American Association for Cancer Research, 2017)
RECQL1, a key member of the RecQ family of DNA helicases, is required for DNA replication and DNA repair. Two recent studies have shown that germline RECQL1 mutations are associated with increased breast cancer susceptibility. Whether altered RECQL1 expression has clinicopathologic significance in sporadic breast cancers is unknown. We evaluated RECQL1 at the transcriptomic level (METABRIC cohort, n = 1,977) and at the protein level [cohort 1, n = 897; cohort 2, n = 252; cohort 3 (BRCA germline deficient), n = 74]. In RECQL1-depleted breast cancer cells, we investigated anthracycline sensitivity. High RECQL1 mRNA was associated with intClust.3 (P = 0.026), which is characterized by low genomic instability. On the other hand, low RECQL1 mRNA was linked to intClust.8 [luminal A estrogen receptor-positive (ER+) subgroup; P = 0.0455] and intClust.9 (luminal B ER+ subgroup; P = 0.0346) molecular phenotypes. Low RECQL1 expression was associated with shorter breast cancer-specific survival (P = 0.001). At the protein level, low nuclear RECQL1 level was associated with larger tumor size, lymph node positivity, high tumor grade, high mitotic index, pleomorphism, dedifferentiation, ER negativity, and HER-2 overexpression (P < 0.05). In ER+ tumors that received endocrine therapy, low RECQL1 was associated with poor survival (P = 0.008). However, in ER- tumors that received anthracycline-based chemotherapy, high RECQL1 was associated with poor survival (P = 0.048). In RECQL1-depleted breast cancer cell lines, we confirmed doxorubicin sensitivity, which was associated with DNA double-strand breaks accumulation, S-phase cell-cycle arrest, and apoptosis. We conclude that RECQL1 has prognostic and predictive significance in breast cancers.